Fetal Ovarian Cysts Diagnosed During Prenatal Ultrasound Screening - K. Emre Karaşahin; Kazim Gezginç; Mustafa Ulubay; Ali Ergün (Elsevier, 2008)
Objective: To discuss the follow-up and management of fetal ovarian cysts (FOCs) and review the current literature. Case Report: A 26-year-old, gravida 2, para 0, abortus 1, Rh-negative patient was diagnosed with bilateral FOCs during ultrasound examination at 32 weeks' gestation. Fetal nuchal translucency measured at 1 2 weeks' gestation was 1.2 mm, and a combined triple test fortrisomy 21 suggested a 1/800 risk. She was regularly monitored at our antenatal outpatient clinic, and the course of her pregnancy was uncomplicated until 32 weeks' gestation, when bilateral FOCs were diagnosed. Because of cephalopelvic disproportion, a cesarean section was performed at 39 weeks' gestation and a 3,680-g Rh-positive female baby was delivered. The baby was admitted to the neonatal care unit and was monitored by pediatricians. Ultrasound examination in the second postpartum month revealed spontaneous regression of the bilateral ovarian cysts. Conclusion: Although FOCs are not usually life-threatening, the risk of losing the ovaries due to torsion during the neonatal period and the resulting sexual development disorders and infertility are very disturbing. [Taiwan J Obstet Cynecol 2008;47(2):215-217]